Prospective evaluation of patient-reported outcomes of invisible ink tattoos for the delivery of external beam radiation therapy: the PREFER trial - Hardy-Abeloos, Camille; Gorovets, Daniel; Lewis, Aurora; Ji, Wenyan; Lozano, Alicia; Tung, Chih Chun; Yu, Francis; Hanlon, Alexandra; Lin, Haibo; Kha, Anh; Yamada, Yoshiya; Kabarriti, Rafi; et al. (Frontiers in Oncology, 2024)
Introduction Invisible ink tattoos (IITs) avoid cosmetic permanence of visible ink tattoos (VITs) while serving as more reliable landmarks for radiation setup than tattooless setups. This trial evaluated patient-reported preference and feasibility of IIT implementation. Methods and materials In an IRB-approved, single institution, prospective trial, patients receiving proton therapy underwent IIT-based treatment setup. A survey tool assessed patient preference on tattoos using a Likert scale. Matched patients treated using our institutional standard tattooless setup were identified; treatment times and image guidance requirements were evaluated between tattooless and IIT-based alignment approaches. Distribution differences were estimated using Wilcoxon rank-sum tests or Chi-square tests. Results Of 94 eligible patients enrolled, median age was 58 years, and 58.5% were female. Most common treatment sites were breast (18.1%), lung (17.0%) and pelvic (14.9%). Patients preferred to receive IITs versus VITs (79.8% pre-treatment and 75.5% post-treatment, respectively). Patients were willing to travel farther from home to avoid VITs versus IITs (p<0.01). Females were willing to travel (45.5% vs. 23.1%; p=0.04) and pay additional money to avoid VITs (34.5% vs. 5.1%; p<0.01). Per-fraction average +treatment time and time from on table/in room to first beam were shorter with IIT-based vs. tattooless setup (12.3min vs. 14.1min; p=0.04 and 24.1min vs. 26.2min; p=0.02, respectively). Discussion In the largest prospective trial on IIT-based radiotherapy setup to date, we found that patients prefer IITs to VITs. Additionally, IIT-based alignment is an effective and efficient strategy in comparison with tattooless setup. Standard incorporation of IITs for patient setup should be strongly considered.